2023
DOI: 10.3390/foods12163044
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Drivers behind the Consumption of Dietary Supplements by Leisure-Time Athletes

Abstract: The prevalence of dietary supplement use has been growing continuously worldwide. Nevertheless, limited research evidence is available on dietary supplement usage related to the segment of leisure-time athletes with the determinants of motivational drivers, sport types, and demographic characteristics. This research, which was conducted in Hungary among leisure-time athletes, aims to learn about the demographic and sports characteristics of consumers who identified themselves as active dietary supplement consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This is aligned with the results of Sirico [46], which found that the enhancement of sport performance and overall health and wellness are primary motivations for supplement use. Additionally, Kovács' [44] study discovered that health preservation and physical well-being were the primary reasons for taking food supplements due to individual motivations, psychological factors, and the recognition of the interconnectedness between nutrition and overall well-being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is aligned with the results of Sirico [46], which found that the enhancement of sport performance and overall health and wellness are primary motivations for supplement use. Additionally, Kovács' [44] study discovered that health preservation and physical well-being were the primary reasons for taking food supplements due to individual motivations, psychological factors, and the recognition of the interconnectedness between nutrition and overall well-being.…”
Section: Discussionmentioning
confidence: 99%
“…They underscored that the respondents' pursuit of maintaining good health is a priority. Likewise, Kovács [44] found that leisure-time athletes primarily took supplements as a proactive measure to maintain their health. These findings collectively highlighted the trend of individuals engaging in behaviors aimed at improving their health.…”
Section: H3mentioning
confidence: 99%